Gambaran Tingkat Pengetahuan, Sikap, dan Prilaku Pencegahan Penyakit Pedikulosis Kapitis pada Anak-Anak di Panti Asuhan Hasami Kasih Tahun 2024 - Wahyu, Wahyu; Panjaitan, Rudyn; Sibuea, Christine (Nommensen Journal of Medicine, 2025)
Background: Pediculosis capitis is a common head lice infestation among children, particularly in environments with suboptimal hygiene, such as orphanages. A lack of knowledge, attitudes, and preventive behaviors can increase the risk of disease transmission. Objective: To determine the level of knowledge, attitudes, and preventive behaviors regarding pediculosis capitis among children at Hasami Kasih Orphanage, Medan, in 2024. Methods: This study employs a descriptive method with a cross-sectional approach. A total of 15 children who met the inclusion and exclusion criteria were selected using purposive sampling. Data were collected through questionnaires and analyzed descriptively using computer software. Results: The findings show that most respondents were aged 9–13 years (66.7%) and were male (73.3%). The prevalence of pediculosis capitis was 26.6%, occurring exclusively in female respondents. The majority of respondents had good knowledge (66.7%) and very positive attitudes (66.7%) toward prevention. However, preventive behavior was still in the moderate category (80%). Conclusion: The children in this orphanage generally have good knowledge and attitudes regarding pediculosis capitis prevention. However, preventive behavior still needs improvement. Further research is needed to identify other factors influencing the occurrence of pediculosis capitis and to examine the relationship between knowledge, attitudes, and preventive behaviors in infestation cases.